Invertebrate colonization on artificial substrates in a coral reef at Gorgona Island, Colombian Pacific Ocean - Lozano-Cortés, Diego F (2014)
Habitat colonization is a fundamental process in marine population dinamics and community ecology. Marine invertebrate colonization of artificial hard substrates and its spatial variation was studied over the course of one year at La Azufrada coral reef, Gorgona Island, Colombia. Five sets of artificial plates (terracotta and ceramic) were deployed parallel to the bottom in each of three reef zones (backreef, flat and slope). Plates were recovered after 12 months of their installation. The community that developed on the artificial substrate plates was composed of 24 taxa, among which corals were remarkably absent. Species richness on plates did not differ between reef zones, type of plate material or plate surfaces. The resulting community was dominated by barnacles (Balanus trigonus) with a mean density of 26 787.8 (±47 301.0) individuals/m2 (mean±1S.D.). The density of this species was significantly higher on plates deployed on the reef slope than on the reef flat or back reef, and was lower on the upper than on the lower or lateral surfaces of plates. The dominance of B. trigonus on artificial plates during this experiment suggests a possible synergistic effect between its reproductive traits and competitive ability for space, which prevents the successful recruitment of other reef organisms such as corals. Rev. Biol. Trop. 62 (Suppl. 1): 161-168. Epub 2014 February 01.